2022
DOI: 10.1270/jsbbs.21076
|View full text |Cite
|
Sign up to set email alerts
|

Allelic variation and genetic diversity of HMW glutenin subunits in Chinese wheat (<i>Triticum aestivum</i> L.) landraces and commercial cultivars

Abstract: Wheat landraces have abundant genetic variation at the Glu-1 loci, which is desirable germplasms for genetic enhancement of modern wheat varieties, especially for quality improvement. In the current study, we analyzed the allelic variations of the Glu-1 loci of 597 landraces and 926 commercial wheat varieties from the four major wheat-growing regions in China using SDS-PAGE. As results, alleles Null, 7+8, and 2+12 were the dominant HMW-GSs in wheat landraces. Compared to landraces, the commercial varieties con… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

6
9
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(15 citation statements)
references
References 56 publications
6
9
0
Order By: Relevance
“…Moreover, 15 alleles were found at the Glu-1 locus in commercial cultivars from China by Gao et al [28]. Wang et al [21] reported 14 alleles in 131 commercial varieties of wheat in the middle and lower Yangtze River region. In the study of Farahani et al [29], 12 alleles were identified in Iranian commercial bread wheat cultivars.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, 15 alleles were found at the Glu-1 locus in commercial cultivars from China by Gao et al [28]. Wang et al [21] reported 14 alleles in 131 commercial varieties of wheat in the middle and lower Yangtze River region. In the study of Farahani et al [29], 12 alleles were identified in Iranian commercial bread wheat cultivars.…”
Section: Discussionmentioning
confidence: 99%
“…The SDS-PAGE method reported by Wang et al [21] was used to identify the HMW-GS compositions. First, 40 mg of flour was added with 600 µL of SDS-PAGE buffer [62.5 mM Tris-HCl, pH 6.8, 2% (w/v) SDS, 10% (v/v) glycerol, 5% (v/v) 2-mercaptoethanol, 0.002% (w/v) bromophenol blue], and well shaken for 30 min.…”
Section: Sds-page Analysismentioning
confidence: 99%
“…For HMW-GS characterization, a single kernel was ground to fine powder for the identification of HMW-GS. About 10 mg of flour was taken in 400 μL of SDS-PAGE protein extraction buffer as previously described in ref . The SDS-PAGE gel analysis and electrophoresis were accomplished according to the methodology previously discussed in refs and .…”
Section: Methodsmentioning
confidence: 99%
“…60,61 The higher bread making quality is related to some HMW-GS subunits like 1Dx5+1Dy10, 1Bx14+1By14, and 1Ax1, whereas the dough strength is adversely affected by the presence of subunits like 1Dx2+11Dy12 and 1Bx20, and the bread making quality is positively affected by the subunits 1Dx17+1Dy18 and 1Ax2*. 54,59,62 Foliar application of micronutrients is an essential technique for increasing grain micronutrient contents and crop yields. Foliar application of Cu and B enhanced the growth and yield related attributes of wheat crop.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation